Закономірності утворення епоксиду під час активування Мо2 В в реакції β-етилаліл-α-етилакрилату з трет-бутилгідропероксидом - Комаренська, З. М.; Олійник, Л. П.; Макота, О. І.; Komarenska, Z. M.; Oliynuk, L. P.; Makota, O. I. (Lviv Politechnic Publishing House, 2005)
Досліджено закономірності утворення епоксиду в період активування каталізатора Мо2В в реакції взаємодії β-етилаліл-α-етилакрилату з трет-бутилгідропероксидом. Досліджено зміну складу поверхні каталізатора Мо2В і його кількості в реакційній суміші, а також продуктів реакції (трет-бутилового спирту й2,3-епокси-2-етилпропілетилакрилату). Показано, що селективність утворення епоксиду не є постійною. Встановлено, що гідропероксид на неактивованій формі каталізатора витрачається непродуктивно, а на активованій повністю витрачається на епоксидування.

The regularities of epoxide formation during the activation of the Mo2B catalyst in the reaction of β- ethylalyl-α-ethyl acrylate interaction with tert-butyl hydroperoxide have been studied. The change in the composition of the Mo2B catalyst surface and its amount in the reaction mixture was studied. As well as reaction products (tert-butyl alcohol and 2,3-epoxy-2-ethylpropylethyl acrylate). It is shown that the selectivity of epoxy formation is not constant. It was found that the hydroperoxide on the non-activated form of the catalyst is consumed unproductively, and on the activated completely spent on epoxidation.
Regularities of epoxide formation during the activation of Mo2B in the reaction of β-ethylalyl-α-ethyl acrylate with ter-butyl hydroperoxide
Keywords: окиснення; епоксидування; кінетичні закономірності; каталізатор; β-етилаліл-α-етилакрилат; oxidation; epoxidation; kinetic regularities; catalyst; β-ethylalyl-α-ethyl acrylate